2021
DOI: 10.31235/osf.io/76gxv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Representation in Saudi EFL Textbooks: A Study of the Family and Friends Series

Abstract: The aim of the present study was to investigate the gender representation in the English as a Foreign Language textbook, Family and Friends 6 KSA second edition, that is designed internationally and widely used in private Saudi elementary schools. To achieve the study goals, a mixed method was used, content analysis and a compiling quantitative data in which the corpus of the English textbook was analyzed; frequencies and percentages of gender appearances and activities were also calculated. The major findin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This issue may not reflect reality in much of the actual world, particularly in Saudi Arabia, where major demographic changes are occurring at a rapid pace, particularly among women. They are now looking for more equality and hope for a more gender-equal society, and textbooks should reflect this as much as feasible (Almghams, 2020). The results of the study showed the low rates of women empowerment in social, economic, and political empowerment dimensions and highlighted some women's issues in the books of the three grades of the secondary stage.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This issue may not reflect reality in much of the actual world, particularly in Saudi Arabia, where major demographic changes are occurring at a rapid pace, particularly among women. They are now looking for more equality and hope for a more gender-equal society, and textbooks should reflect this as much as feasible (Almghams, 2020). The results of the study showed the low rates of women empowerment in social, economic, and political empowerment dimensions and highlighted some women's issues in the books of the three grades of the secondary stage.…”
Section: Discussionmentioning
confidence: 90%
“…Saudi Arabia is currently undergoing considerable long-term changes, particularly in terms of female roles and opportunities. Starting with the support of women's education, which allows women to work in various sectors, the process of empowering Saudi women has achieved important milestones on social, economic, and political levels (Almghams, 2020). Furthermore, Saudi society has paid attention to the issue of women's empowerment in successive eras (Bin Arab World English Journal www.awej.org ISSN: 2229-9327 5 Husain, 2019).…”
Section: Efl Contextmentioning
confidence: 99%
“…In the specific context of Saudi Arabia, only four studies have focused on the (mis) representation of women in EFL textbooks ( Al-Jumiah, 2016 ; Sulaimani, 2017 ; Aljuaythin, 2018 ; Almghams, 2020 ). In the first study, Al-Jumiah (2016) explored how social power and gender ideology were represented in two high school EFL textbooks in use in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Almghams (2020) studied the gender representation in the second edition of Family and Friends KSA , which was published by Oxford University Press in 2017. This textbook is used predominantly in private schools in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation